"Interprofessional collaboration" among pharmacists, physicians, and nurses: A hybrid concept analysis - Faeze Kobrai-Abkenar; Sanaz Salimi; Parand Pourghane (Wolters Kluwer Medknow Publications, 2024)
Background: "Interprofessional Collaboration" is associated with improving the quality of care. The objective of this study was the analysis of the concept of "Interprofessional Collaboration" using a hybrid model. Materials and Methods: A hybrid model was used in order to analyze the concept of "Interprofessional Collaboration." The first phase was the scientific search of texts in all valid electronic databases. The second phase includes fieldwork in which medical, pharmaceutical, and nursing staff were interviewed. Data were collected, reviewed, and analyzed in the third phase. Results: The four main themes extracted in the theoretical phase included: "attributes of individual, team, organizational, and system." In the fieldwork phase, three themes and seven sub-themes were identified: "Dynamism/effectiveness of collaboration, uncertain boundaries of collaboration, advanced organizational culture." In the final phase, with the combination of the results of two previous phases, the final definition of the concept was presented: "A process that brings together systems, organizations and individuals from various professions to achieve common interests and goals. Achieving common goals and interests is influenced by individual, team, organizational, and system attributes." Conclusions: Defining the concept of interprofessional collaboration and identifying its various aspects can be a practical guide for creating and evaluating it in educational and clinical settings.